‘I Have Won, and I Want to Share It’: The Ways Female Skiers Use Facebook as a Communication Tool - Macková, Veronika; Turková, Kateřina (Communication Today, 2025)
The study examines the presence of female skiers, with and without a disability, on the social media platform Facebook. It focuses on Czech and foreign athletes and discusses their posts, as well as promotional and commercial content published on their official Facebook pages. The study is based on a quantitative and qualitative analysis of the published content (i.e. texts, photos and videos, links, hashtags), taking into consideration fans’ reactions posted on the official Facebook pages of the selected athletes. Personal Facebook pages of four female athletes are reflected on. These athletes were successful at the World Championships in 2017. To provide consistency, all of the selected athletes are skiers (Tereza Kmochová – the Czech hearing impaired alpine skier, Šárka Strachová – the Czech alpine skier, Henrieta Farkašová – the Slovak visually impaired alpine skier and Mikaela Shiffrin – the American champion in alpine skiing). Three key research questions are posed: How the female skiers in question use their official Facebook pages for communication, promotional and commercial purposes? What are the similarities and differences present in Facebook communication of the female athletes with and without a disability? What are the similarities and differences in Facebook communication of these Czech and foreign skiers? The results prove, for example, that the ablebodied athletes post significantly more content on their official Facebook pages than the athletes with the aforementioned disabilities. Moreover, Tereza Kmochová who also participates in standard competitions tends to post more promotional content than Henrieta Farkašová who competes only in para alpine skiing.